Computer technology and computer programming : new research and strategies - Antonakos, James L. (Apple Academic Press, 2011)
"This new book covers a broad range of new work in computer technology and programming. Topics include encryption techniques, SQL generation, Web 2.0 technologies, visual sensor networks, reconfigurable computing, video streaming, animation techniques, and more. Readers will also learn about an educational tool and game to help students learn computer programming and a new medical technology paradigm centered on wireless technology and cloud computing designed to overcome the problems of increasing health technology costs."